2022
DOI: 10.1021/acs.jmedchem.2c00471
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Bioevaluation of a Novel Hybrid Molecular Pyrrolobenzodiazepine–Anthracenecarboxyimide as a Payload for Antibody–Drug Conjugate

Abstract: A novel series of hybrid molecules combining pyrrolobenzodiazepine (PBD) and anthracenecarboxyimide pharmacophores were designed, synthesized, and tested for in vitro cytotoxicity against various cancer cell lines. The most potent compound from this series, 37b3, exhibited a subnanomolar level of cytotoxicity with an IC50 of 0.17–0.94 nM. 37b3 induced DNA damage and led to tumor cell cycle arrest and apoptosis. We employed 37b3 as a payload to conjugate with trastuzumab to obtain the antibody–drug conjugate (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Previous studies have also reported similar observations, highlighting the potential of hydrophilic and rigid spacers to improve assay sensitivity and specificity. It has also been previously reported that the spacer length does not bear any correlation with the assay sensitivity in ELISA ( 1 5 , 11 , 19 , 20 ) as it does have an effect in some other immunoassays and auxiliary binding systems ( 9 11 , 20 ). The use of a hydrophilic and rigid spacer possibly helped in projecting the hapten away from the enzyme, leading to an enhanced antibody binding signal and improved sensitivity of the assay ( 9 11 , 14 , 20 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have also reported similar observations, highlighting the potential of hydrophilic and rigid spacers to improve assay sensitivity and specificity. It has also been previously reported that the spacer length does not bear any correlation with the assay sensitivity in ELISA ( 1 5 , 11 , 19 , 20 ) as it does have an effect in some other immunoassays and auxiliary binding systems ( 9 11 , 20 ). The use of a hydrophilic and rigid spacer possibly helped in projecting the hapten away from the enzyme, leading to an enhanced antibody binding signal and improved sensitivity of the assay ( 9 11 , 14 , 20 ).…”
Section: Discussionmentioning
confidence: 95%
“…It is not always easy to develop a specific and sensitive ELISA for a small molecule such as prednisolone, a synthetic steroid that is not naturally present in the body. One of the most important factors that determine the sensitivity and specificity is the combination of antibody and enzyme conjugate used in the assay (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…As a more general cathepsin substrate, Val‐Ala has been widely used in the construction of novel ADCs in recent years, which can be cleaved by more than one cathepsin expressed in various tumors. [ 3 , 45 , 46 ] Therefore, we constructed a Val‐Ala‐based dipeptide linker‐payload fragment, which exhibited better payload release efficiency than the GGFG linker in the CTSB cleavage system (Figure 3C ). Although the introduction of the cyclobutyl group still had a certain effect on linkers’ cleavage, compared with NAC‐GGFG‐Ed9, the release rate of NAC‐VA‐Ed9 (3.07±0.87%) recovered to a level similar to NAC‐GGFG‐DXd (2.99±0.54%).…”
Section: Resultsmentioning
confidence: 99%